2009
DOI: 10.1159/000259897
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Glycation and Anti-Albuminuric Effects of GLY-230 in Human Diabetes

Abstract: Background/Aims: Inhibiting nonenzymatic glycation with GLY-230 lowers glycated albumin without affecting hyperglycemia and ameliorates renal dysfunction in the db/db mouse, but the effects of this compound in man have not been assessed. We report results from the first clinical trial in patients with diabetes of this new glycation inhibitor. Methods: 21 diabetic men were randomly assigned to receive a total dose of 250, 500 or 750 mg of GLY-230 or placebo (1:1:1:1.2 ratio) daily for 14 days to evaluate safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…GLY-230 reduced glycated albumin and albuminuria compared to baseline but not placebo. 191 AGE crosslink breakers, such as alegebrium, and inhibitors of the AGE receptor have shown benefit in DN models but have not been studied in humans.…”
Section: Age Inhibitorsmentioning
confidence: 99%
“…GLY-230 reduced glycated albumin and albuminuria compared to baseline but not placebo. 191 AGE crosslink breakers, such as alegebrium, and inhibitors of the AGE receptor have shown benefit in DN models but have not been studied in humans.…”
Section: Age Inhibitorsmentioning
confidence: 99%
“…GLY-230 [2-(3-chlorophenylamino)phenylacetic acid] is a new small molecule that inhibits modification of albumin by Amadori glucose adducts. In a small clinical trial of GLY-230 in patients with diabetes, GLY-230 significantly reduced albuminuria (92). Pyridoxamine has been shown to have an anti-AGE effect and is currently under investigation in a phase 2 clinical trial (https://clinicaltrials.gov/).…”
Section: Animal Modelsmentioning
confidence: 99%
“…In preclinical studies in diabetic animal models, GLY-230 significantly reduced Amadori-albumin, decreased urine albumin excretion, restored glomerular nephrin, downregulated TGF-β 1 and VEGF overexpression, ameliorated matrix accumulation, histomorphometric changes and the development of renal insufficiency as well as vitreous alterations (Cohen et al 2002, 2005, 2007, 2008). A recent study in diabetic man demonstrated that GLY-230 lowers glycated albumin and that this decrease is associated with a reduction in urine albumin excretion in patients with pre-existing microalbuminuria (Kennedy et al 2010). …”
Section: Therapies Interfering In the Glycation Pathwaymentioning
confidence: 99%